Mengartikulasikan Suara Alternatif Muslim Asia Tenggara - Wahyudi Akmaliah (Studia Islamika, 2020)
Noorshahril Saat and Azhar Ibrahim (eds). 2020. Alternative Voices in Muslim Southeast Asia: Discourse and Struggle. Singapore: ISEAS Yusuf Ishak Institute.Many scholars in the national and international level have confirmed the conservative Islamic turn in the post of the New Order regime. Nevertheless, to examine this Islamic expression with the conservative interpretation without creating a comparison with the Southeast Asian countries is a problem. In the agency level, whether book translations and circulations, as well as both Islamic thinkers and religious authorities (ustadz), they shape the inter-referencing by looking at each other and referencing one and another as the part of exchange knowledge among the Muslim Southeast Asian. By examining the Southeast Asian countries (Indonesia, Malaysia, and Singapore), this book that consists of the thirteen writers, explains the wave of Islamic conservatism within Muslim societies. Unlike other works that are only describing the wave, this book offers the alternative voices of those subjects that could resist with their ways.